School principal leadership strategies in improving teacher performance - Abidin, Zainal; Ibrahim, Rustam (Universitas Negeri Semarang, 2023)
A teacher's performance can be said to be quality if it produces good work and can lead students to achieve achievement. The aims of this research are: 1) to describe and analyze the principal's leadership strategy planning in improving teacher performance, 2) to describe and analyze the implementation of the principal's leadership strategy in improving teacher performance, 3) to describe and analyze the evaluation of the principal's leadership strategy in improving teacher performance at SMAIT Al Hikmah Boyolali. The research approach used is qualitative. Qualitative research design goes through three stages, namely: orientation, focused exploration, and data analysis. Data collection techniques are interviews, observation and documentation. This research uses triangulation techniques. Data analysis in three steps: data reduction, presenting data, and drawing conclusions. The research results show that: 1) planning to improve teacher performance is carried out by the school principal with all teachers. The school principal provides discipline and role modeling. 2) implementation of improving teacher performance is carried out by the school principal by carrying out seminars and training activities, collaborating with other educational institutions, bringing in experts, holding regular academic supervision, providing complete facilities and infrastructure at the school. 3) evaluation in improving teacher performance is focused on aspects of planning and implementing activities. Conclusion The principal's leadership strategy in improving teacher performance consists of three activities, namely, planning, implementation and evaluation. The author suggests that principals are expected to pay more attention to planning, implementation and evaluation aimed at improving performance. This study uniquely contributes to the understanding of how school leadership can directly influence teacher effectiveness, offering valuable insights for school administrators aiming to improve educational outcomes.